Defining Membership Along the U.S.-Canadian Borderlands: A Case Study of the Baawating Region - Hele, Karl (Ontario History)

(untitled) (The Ontario Historical Society, 2025)
As a case study set within the Sault Ste. Marie-Baawating region, this paper seeks to address the development and implementation of residency requirements to maintain treaty rights in British Canada. Following the conclusion of the War of 1812, British Canada began imposing both unofficial and official decisions relating to receiving gifts, annuities, land rights, and various forms of government assistance. Beginning by limiting gifts to British resident Indians between 1840–1858, the practice evolved into a legislated section of the Indian Act from 1876 to 1951 that removed individuals from Band lists for residing in a foreign country for five consecutive years. Garden River First Nation, a Band within the Baawating region, lost members prior to 1876 based on U.S. residency and acceptance of American annuities, lands, or government assistance. From 1876 to 1951 the Band and its membership continued to be negatively affected by the residency rule. Regardless, the Band continued to contest removals and seek reinstatement of members through calls to treaty rights and understandings of the five-year rule—residency on the reserve or their non-consecutive residence in the U.S. As such, this article explores an understudied aspect of enfranchisement policies within the Indian Act, from their development to formal implementation, Anishinaabeg contestation of these policies, and briefly addresses the ongoing contemporaneous existence of these policies.